ANALISIS PERBANDINGAN PEMANFAATAN APBD POS BELANJA DI DAERAH PEMILIHAN PETAHANA DAN NON PETAHANA - Alwan Sri Kustono; Wulan Pangestu; Rochman Effendi (Universitas Agung Podomoro, 2020)
This research aims to know the fairness level of significance increase on expenditure items in incumbent election area compare with non incumbent election area, and non-election area. This research use secondary data. Data analyze method use comparative description method which describe the result from our data observation that will be compared with one observation subject and other observation subject. The result shows that all of expenditure items not used as politicization object by incumbent. It’s because of increasing expenditure items trend not only occur on incumbent area, but also on some non incumbent area and some non-election area. Significance increase on incumbent area can not conclude as politicization budget and expenditure area by incumbent to preserve their power.